ANALISIS PENDEKATAN DAN MODEL PENGEMBANGAN KURIKULUM BAHASA ARAB DI SEKOLAH DASAR ISLAM SAHABAT BERLIAN GENDONG LAREN LAMONGAN - Umroh, Ida Latifatul; Fatimah, Fatimah; Khoiroh, Hani'atul (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
Changes in the curriculum in Indonesia occur in line with the development of science and technology, the needs of students, and graduate users. Every curriculum that is carried out comes from the Minister of Education as the holder of the Education policy. The curriculums issued have a foundation and construction in their development. The foundation and construction are in the form of curriculum development approaches and models. Based on this, the researcher wants to analyze the approach and model of Arabic curriculum development at SDI Sahabat Berlian Gendong Laren Lamongan. This research is qualitative descriptive, with data sourced from observations, interviews, and documentation. The data analysis is carried out by data collection, reduction, presentation, and conclusion drawn. The results of this study are: (1) The curriculum development approach used by SDI Sahabat Berlian Gendong is a combination of Top Down and Grass roots approaches. (2) The curriculum development model applied at SDI Sahabat Berlian Gendong is the Taba model.